2002
DOI: 10.1161/01.str.0000013562.73522.82
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Angiography for the Evaluation of Carotid Atherosclerotic Plaque

Abstract: Background and Purpose-The goal of this study was to determine the efficacy of CT angiography for the characterization of plaque morphology and composition in carotid atherosclerotic disease. Methods-Fifty-five patients undergoing carotid endarterectomy were imaged preoperatively with single-slice spiral CT angiography. One hundred sixty-five endarterectomy sections were examined histologically at selected levels through the distal common and proximal internal carotid arteries. Plaque density was measured (in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
1
4

Year Published

2005
2005
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 43 publications
6
72
1
4
Order By: Relevance
“…Distal ulcerations are uncommon. Furthermore, we demonstrated that ulcerations are much more common in fatty versus calcified plaques and confirmed the results of Walker et al 18 The relationship between plaque morphology and clinical behavior in the carotid circulation has been incompletely studied, but it has been demonstrated that cerebral infarcts are more frequent in patients with a lipid core than in patients without a lipid core. 33 The presence of a lipid core is significantly associated with cerebral infarction on MR imaging, and particular centrum semiovale infarcts are more frequent than cortical ones.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Distal ulcerations are uncommon. Furthermore, we demonstrated that ulcerations are much more common in fatty versus calcified plaques and confirmed the results of Walker et al 18 The relationship between plaque morphology and clinical behavior in the carotid circulation has been incompletely studied, but it has been demonstrated that cerebral infarcts are more frequent in patients with a lipid core than in patients without a lipid core. 33 The presence of a lipid core is significantly associated with cerebral infarction on MR imaging, and particular centrum semiovale infarcts are more frequent than cortical ones.…”
Section: Discussionsupporting
confidence: 91%
“…24 We demonstrated that MDCTA has a very a high sensitivity (93.75%) and specificity in detecting carotid artery plaque ulcerations. The sensitivity that we reported is higher compared with the works of Link et al, 41 Schwartz et al, 42 Debernardi et al, 24 Oliver et al, 10 and Walker et al 18 ; in these works, however, single-section CT scanners were used. We performed CTA examinations with a multidetector row scanner, and we studied each examination with axial and multiple postprocessed reconstructed images (MIP, MPR, SSD, and VR).…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations